2016
DOI: 10.3389/fonc.2016.00090
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for Community Education Prior to Clinical Trial Recruitment for a Cervical Cancer Screening Intervention in Uganda

Abstract: IntroductionCommunity engagement and education can improve acceptability and participation in clinical trials conducted in Kisenyi, Uganda. In preparation for a randomized controlled trial exploring different methods for cervical cancer screening, we explored optimal engagement strategies from the perspective of community members and health professionals.MethodsWe conducted key informant interviews followed by serial community forums with purposeful sampling and compared the perspectives of women in Kisenyi (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“… 19 In prior ASPIRE research on community engagement and education leading up to a cervical cancer clinical trial, women in the Kisenyi district indicated male involvement was central to the success of any cervical cancer screening intervention. 9 In this group of men, even after the education session, some were still unsure of the risk factors for cervical cancer, and there remained confusion around how HPV transmission and treatment occurred. These findings highlight that a one-time didactic education session may not be sufficient for knowledge translation and the need for ongoing culturally appropriate education programs for both men and women about cervical cancer and HPV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 19 In prior ASPIRE research on community engagement and education leading up to a cervical cancer clinical trial, women in the Kisenyi district indicated male involvement was central to the success of any cervical cancer screening intervention. 9 In this group of men, even after the education session, some were still unsure of the risk factors for cervical cancer, and there remained confusion around how HPV transmission and treatment occurred. These findings highlight that a one-time didactic education session may not be sufficient for knowledge translation and the need for ongoing culturally appropriate education programs for both men and women about cervical cancer and HPV.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research led by this team explored strategies for community engagement and education from the perspective of women and health care providers and identified that the lack of male involvement was a key barrier to cervical cancer screening. 9 …”
Section: Introductionmentioning
confidence: 99%
“…More than half of the women diagnosed with cervical cancer have not attended screening in the past 3 years. A community-based screening strategy is one of the greatest success stories in cancer prevention, and widespread screening reduces the cervical cancer incidence worldwide [38][39][40][41][42]. The mean time between the virus infection and invasive cancer takes about 15 years, and within 2-4 years of detection 15.5-25.5% of low-grade epithelial lesions become high-grade lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous other examples of community engagement that improves cancer screening trial recruitment in underserved populations can be cited, including many studies aiming to account for cultural differences in a trial ( 38 ). For example, Wood et al.…”
Section: Use Of Community Engagement In Cancer Screening and Mced Trialsmentioning
confidence: 99%